U C Berkeley Co-op Friends Annual Heavy-Sacramento - Watkins, Howard::::::::: (1983)
Frank Gumpert, Alan Pricco, Teresa Pricco, Janie Gumpert, Janice Rau, Steven Rau, Bonnie Neary, Jerry Neary, David Atkinson, Denise Morse, Kathy Muniz